Thrombosis risk assessment in patients with congenital thrombophilia during COVID - 19 infection. Issue 218 (October 2022) - Kovac, Mirjana; Mitic, Gorana; Milenkovic, Marija; Basaric, Dusica; Tomic, Branko; Markovic, Olivera; Zdravkovic, Marija; Ignjatovic, Vera
Abstract: Background: Coagulation dysfunction represents a serious complication in patients during the COVID-19 infection, while fulminant thrombotic complications emerge as critical issues in individuals with severe COVID-19. In addition to a severe clinical presentation, comorbidities and age significantly contribute to the development of thrombotic complications in this disease. However, there is very little data on association of congenital thrombophilia and thrombotic events in the setting of COVID-19. Our study aimed to evaluate the risk of COVID-19 associated thrombosis in patients with congenital thrombophilia. Methods: This prospective, case-control study included patients with confirmed COVID-19 infection, followed 6 months post-confirmation. The final outcome was a symptomatic thrombotic event. In total, 90 COVID-19 patients, 30 with known congenital thrombophilia and 60 patients without thrombophilia within the period July 2020–November 2021, were included in the study. Evaluation of hemostatic parameters including FVIII activity and D-dimer was performed for all patients at 1 month, 3 months and 6 months post-COVID-19 diagnosis. Results: Symptomatic thrombotic events were observed in 7 out of 30 (23 %) COVID-19 patients with thrombophilia, and 12 out of 60 (20 %) without thrombophilia, P  = 0.715. In addition, the two patient groups had comparable localization of thrombotic events, time to thrombotic event, effect of antithrombotic treatment and changes in FVIII activity, while D-dimer level were significantly increased in patients without thrombophilia. Conclusion: Our findings suggest that patients with congenital thrombophilia, irrespective of their age, a mild clinical picture and absence of comorbidities, should receive anticoagulant prophylaxis, adjusted based on the specific genetic defect. Highlights: The risk for VTE may be present several months following a SARS-CoV-2 infection. All asymptomatic carriers of thrombophilia should be placed on prophylactic anticoagulation. The duration and type of prophylaxis should be individually adjusted. The risk for VTE is particularly pronounced in patients with homozygous AT Type II HBS deficiency.